Pengaruh Penggunaan Model Pembelajaran Mind Mapping Pada Pembelajaran Matematika Terhadap Kemampuan Koneksi Matematis Siswa Kelas VIII: Penelitian Eksperimen Di MTs. Bahrul Ulum Singgahan Tahun Pelajaran 2019/2020 - Zulfatun Anisah (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2020)
Mathematical connections are developed in schools that have not been maximized in learning mathematics. Schools generally only tend to improve cognitive and psychomotor aspects. Linear learning only triggers the work of the left brain, while the right brain has not been used optimally, as a result students become impeded. Students do not produce creative ideas in solving problems let alone the ability to understand problems. The purpose of this study is to determine the effect of learning mathematics using mind mapping on students' mathematical connections, and to find out how students respond in learning mathematics using mind mapping. This research is using experimental method. The design of this study that will be examined are two groups (classes), namely the control class and the experimental class. In the control class conventional learning models are used and the experimental class that will be subject to treatment is mind mapping learning. From the results of the study showed that learning mathematics using mind mapping has a positive effect on the ability of students' mathematical connections and the positive response of students to learning mathematics using mind mapping.